PENDAMPINGAN PENGOLAHAN LIMBAH CAIR BATIK DI UMKM BATIK CAHAYA BARU, SEMARANG - Qonitah, Fadilah; Ariastuti, Reni; Dewi, Anita Oktaviana Trisna; Suwardi, Suwardi; Yuliyanti, Andini Dwi; Azizah, Reyza Nur (Jurnal Abdimas Bina Bangsa, 2025)
UMKM Batik Cahaya has been operating since 2015 with the production of stamped batik cloth. Since the establishment of this UMKM, their batik production has produced liquid waste that is not managed properly. The resulting batik liquid waste is only collected and then discharged directly into the environment so that it has the potential to cause negative impacts on the environment Therefore, it is necessary to provide assistance related to the management of batik liquid waste so that it is safe for the environment. This service was carried out by counselling to Batik Cahaya Baru partners and making WWTP (Wastewater Treatment Plant) physically and anaerobic biology with bacterial media, bioballs, palm fibres, split stones and merapi stones. The result of this activity is the implementation of counselling to UMKM Batik Cahaya Baru about the treatment of batik liquid waste and the realisation of  WWTP. Through this programme, the liquid waste management process at UMKM Batik Cahaya Baru can be improved with the WWTP that has been made so that it is hoped that the discharged batik wastewater will not pollute the environment.